OP0195-HPR Comparison of Educational Models for Maintaining Optimal Safety in The Self-Management of Biotherapy amongst Rheumatoid Arthritis and Spondyloarthritis Patients. (15th July 2016) - Fayet, F.; Rodere, M.; Savel, C.; Pereira, B.; Soubrier, M.; Couderc, M.
Abstract : Background: Biotherapies prescribed in patients with rheumatoid arthritis (RA) and spondyloarthritis (SpA) are associated with risks that patients must be aware of. Patient education offers them to learn how to manage such treatments on a day-to-day basis. In our department, patients can benefit from 3 different educational models: individual informational consultation (Model 1), individual consultations including the 4 recommended steps (educational diagnosis, objectives, education and assessment) (Model 2) and individual consultations with group workshops (Model 3). Objectives: To assess which educational model appears the most appropriate for maintaining optimal safety in the self-management of biotherapy. Methods: This is an observational, monocentric, retrospective study on routine care. All patients on biotherapy with at least one educational consultation between 2009 and 2013 were subsequently divided up according to the undergone educational model (Models 1, 2, or 3). During normal management, patients filled out the BIOSECURE questionnaire, meant to assess their theoretical and practical knowledge (clinical cases), prior to consultation with an education nurse. The overall BIOSECURE score, its theoretical and practical subsections, the different dimensions of the questionnaire and the behaviors in risk situations were compared based on the 3 models. Results: In total, 222 patients were included (67% women, age 53.9 years, disease duration: 10 years, RA n=137, SpA n=77 and uncategorized rheumatism n=8, anti-TNF 89.6%, rituximab 3.2%, abatacept 3.6%, and tocilizumab 3.6%. As regards the educational model, 106 patients (47.8%) benefited from Model 1, 88 (39.6%) from Model 2, and 28 (12.6%) from Model 3. The overall BIOSECURE score was 76.6/100 without any significant difference depending upon the educational model (Model 1: 75.1, Model 2: 76.7, Model 3: 81.8; p=0.07). The BIOSECURE score was significantly higher amongst women (p=0.007), young people (p<0.001), working patients (p=0.005), higher education degree holders (p<0.001), patients whose diagnosis was most recent (p=0.008), as well as patients on etanercept (p=0.04) and those on intravenous biotherapies (p=0.004). Model 3 patients displayed a significantly higher practical score (clinical cases) than Model 1 (p<0.001) and 2 (p=0.003) patients. There was also a significant difference in BIOSECURE score in favor of Model 3 in certain skill areas, such as "Patient behavior in case of fever" (p=0.03) and "Behavior when faced with injuries, prevention of infectious complications and vaccination" (p=0.03). In terms of the implementation of acquired knowledge in risk situations, 64.5% of patients displayed appropriate behavior in the event of signs of infection, 68% in the case of surgical intervention, and 65% in the event of dental avulsion, without anydifference depending upon the model. Conclusions: The educational model involving group workshops showed no significant variation from the overall BIOSECURE score amongst patients treated with a biotherapy for RA or SpA when compared to the models based solely on individual consultations. However, patients having participated in group workshops exhibited improvement in practical scores and certain skill areas. Disclosure of Interest: None declared